Analyzing The Strategies on The Success of Hermes Sales - Shen, Jiayi (Transactions on Economics, Business and Management Research, 2024)
The purpose of the study was to explore why Hermes has the highest sales in the Asia-Pacific region. Using Hermès’s sales in Asia Pacific in 2022 and 2023 as a case study, the next part of the analysis will conduct a literature review to delve into the brand’s history in the region. An examination of the factors contributing to its success will follow. Finally, the analysis will conclude with recommendations for the current state of the brand and its operations in the Asia Pacific region. Three primary factors contribute to Hermes’ success. Firstly, since China is the main market in the Asia-Pacific region, Hermès could focus more on the sense of propriety, such as providing surprises to its Very Important Person and Very Important Client customers at Chinese festivals. Secondly, Hermes’ localization strategy prioritizes cultural integration to cater to local consumers’ preferences. It also involves organizing exhibitions to promote the brand’s philosophy and culture. To further expand the market, Hermes could invite celebrities who align with the brand’s values to endorse its products. Lastly, the limited availability of Hermes bags and the distinctive distribution strategy uphold the brand’s high-end luxury reputation. In order to expand its market reach, Hermes can become more varied in its designs. This article can assist Hermes in expanding the number of consumers in the Asia-Pacific region from a variety of angles.